The Effect of Special Treatment Benefits and Confidence Benefits on Consumer Commitment and Consumer Loyalty: A Study on Shopee Users in the Covid 19 Pandemic - Galuh Adisti Maheswari; Anas Hidayat (Journal of Business and Management Review, 2021)
This study aims to determine the effect of Special Treatment Benefits and Confidence benefits on Consumer Commitment and Consumer Loyalty to Shoppe users in the Pandemic Era. Tests in this study using 210 respondents. The sampling technique used in this research is purposive sampling. This study uses the Structural Equation Modeling (SEM) data analysis technique which was developed to test the research hypothesis which was processed using the AMOS version 24 program. The data variables used in this study are Special Treatment Benefits, Confidence Benefits, Consumer Commitment, Consumer Loyalty, these variables form five hypotheses. And the results of the analysis in this study indicate that Special Treatment Benefits have a positive effect on Consumer Commitment, Special Treatment Benefits have a positive effect on Consumer Loyalty, Confidence Benefits have a positive effect on Consumer Commitment, Confidence Benefits have a positive effect on Consumer Loyalty, and Consumer Commitment has a positive effect on Consumer Loyalty.